2021
DOI: 10.1002/aelm.202100369
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide‐Based Flexible Plasma Sheet and Surface Ionization Waves Propagation

Abstract: demands of treating complex 3D targets and irregular surfaces. Typical DBDs can hardly satisfy these requirements due to the narrow discharge gap and the rigid dielectric material. Thus it is of great significance to develop a specific plasma source which not only has the characteristics of high surface-compatibility and large-area coverage, but also maintains light, convenient and economical. The emergence of DBD plasma source using flexible material instead of the rigid one as the dielectric barrier provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Initiating plasma filaments intersected the apex of the hemispheres due to electric enhancement and polarization of the dielectric, followed by SIWs which propagated down the slopes of the hemispheres. Sun et al experimentally and computationally investigated SIWs propagating along a curved polyimide surface sustained with alternating powered and grounded electrodes buried in the dielectric [28]. They found that bending of the thin (100 μm) polymer sheet from being concave to the plasma to convex to the plasma increased electron densities by as much as 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Initiating plasma filaments intersected the apex of the hemispheres due to electric enhancement and polarization of the dielectric, followed by SIWs which propagated down the slopes of the hemispheres. Sun et al experimentally and computationally investigated SIWs propagating along a curved polyimide surface sustained with alternating powered and grounded electrodes buried in the dielectric [28]. They found that bending of the thin (100 μm) polymer sheet from being concave to the plasma to convex to the plasma increased electron densities by as much as 30%.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] That is to say, in order to achieve a faster signal transmission speed, the used dielectrics are required to possess the D k and D f values as low as possible. [14][15][16] Meanwhile, it is also known that the D k and D f values of the electrically insulating polymers are highly related with the water or moisture absorptions of the polymers because the absorbed water with high D k value ($ 80) usually increase the D k values of the polymers. 17 Thus, the polymer dielectrics with excellent combined properties, including high thermal and dimensional stability, low D k and D f values, and low water absorption are highly required for 5G and 6G high-frequency FCCL applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been well established that the delay time of the signal transmission is directly proportional to the signal transmission frequency, and it is also positively correlated with the D k and D f values of the dielectrics, such as the substrates, adhesives, and so on 11–13 . That is to say, in order to achieve a faster signal transmission speed, the used dielectrics are required to possess the D k and D f values as low as possible 14–16 . Meanwhile, it is also known that the D k and D f values of the electrically insulating polymers are highly related with the water or moisture absorptions of the polymers because the absorbed water with high D k value (~ 80) usually increase the D k values of the polymers 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Coplanar DBD (CDBD) which utilizes the thin film as the dielectric could adapt to different surface shapes and treat a relatively large area. However, recent studies reported that the bending condition of CDBD could affect the discharge [28]. The wearable plasma source was proposed which could be used to treat the large area with irregular shapes [29][30][31].…”
Section: Introductionmentioning
confidence: 99%